Design of a Chemistry Learning on Android Media (CHEMONDRO) Assisted by Articulate Storyline to Improve Students’ Motivation and Learning Outcomes in Green Chemistry - Zalfa Dwirakhma Saharani; Kasmui, Kasmui (Chemistry in Education, 2025)
This study aims to design a creative and innovative Android-based chemistry learning media, Chemistry Learning on Android (CHEMONDRO), supported by Articulate Storyline to enhance students’ motivation and learning outcomes, particularly in the topic of green chemistry. The research employs the Research and Development (R&D) method using the Four-D (4D) development model, which was simplified into Three-D (3D): Define, Design, and Develop. The feasibility, effectiveness, and user responses toward the media were the main considerations in this study. CHEMONDRO was validated by experts in both content and media, with results showing a material expert validation score of 97.66%, media expert validation of 97.62%, and teacher validation of 92.86%, indicating a very high level of feasibility. The learning outcome improvement was analyzed using the N-Gain test, which resulted in an average N-Gain of 0.70 and 0.79, categorized as moderate and high improvement. In addition, affective and psychomotor domains of the students showed very good results. Readability testing in a small group reached 95.10%, while the implementation feasibility scored 93.89%. Large-scale student responses showed a very positive result of 94.46%. Based on these findings, CHEMONDRO is considered highly feasible, effective, and well-received as a media tool to support chemistry learning and improve student engagement and outcomes, particularly in green chemistry material.